Synthesis of components for composite material of electrical contacts with unique properties for high-current electrical apparatus with arc-free switching - Hablovska, N.; Pavlenko, T.; Kloc-Ptaszna, A.; Krzemiński, Ł.; Matula, G.; Łukowiec, D.; Kononenko, M.; Hablovskyi, B. (Physics and Chemistry of Solid State, 2024)
Experimental research has determined the optimal composition of components for a composite material used in electrical contacts with unique properties designed for high-current electrical apparatus that perform switching without arc formation. This article presents the results of a study on the porosity of copper obtained by the powder metallurgy method. To analyze the porosity of copper, methods for studying porous structures on both the surface and within the sample were examined. The metallographic method and the method of computed tomography were selected as the most suitable and informative. The conducted studies of the porous material revealed differences in material structure and porosity depending on various manufacturing conditions: temperature, process duration, and ingredient proportions. This, in turn, allowed for the identification of technological parameters for obtaining porous copper with up to 65% porosity, enabling its use as a matrix of the conductive material with a higher melting temperature. The optimal method for infiltrating copper samples with a low-melting material (fusible component) was selected.